Challenges of Developing Novel Vaccines With Particular Global Health Importance - Heaton, Penny M. (Frontiers in Immunology, 2020)
Six of the top ten leading causes of death in low resource settings could potentially be prevented by vaccination. Development of vaccines for individuals in these populations is difficult because of the biological complexity of the prevalent pathogens and the challenges inherent to development of any vaccine. This review discusses those challenges and promising advances to address them and highlights recent progress in development of vaccines against several pathogens of interest.